(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to analyze the influences of Libya’s eGovernment servicesand provide a comprehensive model. The analysis classifies eGovernment adoption in three models: intentions to use eGovernment services, eGovernment readiness model and user’s satisfaction model.A quantitative methodhas been used and questionnaires have been distributed to Libyan citizens online using google form. With its structural equation modelling methodology, 554 responses have been gathered from Libyan citizens by empirically checking the concept. Using PLS packagein the Rprogram for analyzing the data. The main challenge for Libyans is what the critical determinants of their adoption of eGovernment are? Based on an extensive review of relevant literature, ﬁve hypotheses are formulated. Some factors are identiﬁed that may affect the Libyans’ level of satisfaction towards using the Libya eGovernment services.Based on multiple linear regression and factor analyses, our empirical analysis demonstrates several key ﬁndings. These ﬁndings indicate the intention of using eGovernment services and website design as a moderator the key drivers of user’s satisfaction so as to provide feedback in a set of recommendations that will enable creating eGovernment services which are compatible with citizens’ needs, desires, and expectations. Also, we found that user satisfaction is affected by eReadiness and Intentaion to use variables by 64.27 percent and the remaining 35.72 percent was influenced by other variables. Finally, implications and recommendations of these ﬁndings were discussed.